The complete mitochondrial genome of Tyrophagus longior (Acari: Acaridae): gene rearrangement and loss of tRNAs. (October 2015) - Yang, Banghe; Li, Chaopin
Abstract: Most species of the family Acaridae are economically pests for stored grains and growing agricultural crops. However, complete mitochondrial genomes (mitogenomes) and the gene features therein are increasingly used for investigating the mechanism of resistance to acaricides. Herein, we present the complete mitogenome of the acrid mite Tyrophagus longior . Unexpectedly, only 19 transfer RNA genes (tRNAs) were present in the mitogenome of T. longior, lacking trnF, trnS 1 and trnQ . Further, the mitogenome of T. longior was 13, 271 bp in length, and contained 13 protein-coding genes (PCGs) and 2 ribosomal RNAs ( rrnS and rrnL ). The gene order in T. longior was the same as that in T. putrescentiae, yet was distinct from other Acari by gene translocations and/or inversions as well as loss. Twenty-six genes were encoded on the heavy strand (H-strand), while the remaining genes were located on the light strand (L-strand). Most present tRNAs were truncated (48–63 bp, average 53.7 ± 3.07 bp), and lacked either a D- or T-arm. The largest non-coding region (the A + T-rich region) was just 50 bp in length and located between the rrnS and rrnL genes. Although the region was formed a stable stem-loop structure, some structures of microsatellite-like (AT)n and palindromic sequences were not found as previously described in other acarid mites. This information on T. longior mitogenome may help to improve our understanding of the acaricides-resistance mitochondrial genes. Highlights: Gene rearrangements have occurred in Tyrophagus longior mitochondrial genome. Revealing that three tRNA genes of T. longior are lost, lacking trnF, trnQ and trnS1 . Most inferred tRNAs are extremely truncated with the absence of either a D- or T-arm. The longest non-coding region is just 50 bp in length.